Biased trajectory dissemination of uncontrolled mobile sinks for event collection in wireless sensor networks - Guisong Yang; Lijun Wang; Linhua Jiang; Xingyu He (International Journal of Distributed Sensor Networks)
Considering the social properties of mobile sinks, we propose a biased trajectory dissemination of uncontrolled mobile sinks for event collection in wireless sensor networks. In biased trajectory dissemination of uncontrolled mobile sink, we first divide the whole network into clusters which can be managed by cluster heads that are elected in turn for intra-cluster event collection and inter-cluster communication. Second, for a mobile sink, we further divide the clusters it visits into biased clusters and non-biased clusters according to its staying probability. The mobile sink will send its mobility message which shows its location as it moves into a new cluster. We then construct a biased loop which is composed of all biased clusters and some non-biased clusters to disseminate a mobile sink’s mobility message only to clusters on it when the mobile sink moves into a biased cluster. We also construct query path that connects any cluster head that is not on the biased loop to a cluster head on it. An event could be transmitted to the biased loop along the query path for further forwarding to the mobile sink. Numerous simulations show the superior performance of biased trajectory dissemination of uncontrolled mobile sink compared to the representative schemes in terms of average path length, delay, and network energy consumption.